Comparative Morphological, Metabolic and Transcriptome Analyses in elmo1−/−, elmo2−/−, and elmo3−/− Zebrafish Mutants Identified a Functional Non-Redundancy of the Elmo Proteins - Boger, Mike; Bennewitz, Katrin; Wohlfart, David Philipp; Hausser, Ingrid; Sticht, Carsten; Poschet, Gernot; Kroll, Jens (Frontiers in Cell and Developmental Biology, 2022)
The ELMO protein family consists of the homologues ELMO1, ELMO2 and ELMO3. Several studies have shown that the individual ELMO proteins are involved in a variety of cellular and developmental processes. However, it has poorly been understood whether the Elmo proteins show similar functions and act redundantly. To address this question, elmo1 / , elmo2 /- and elmo3 /- zebrafish were generated and a comprehensive comparison of the phenotypic changes in organ morphology, transcriptome and metabolome was performed in these mutants. The results showed decreased fasting and increased postprandial blood glucose levels in adult elmo1-/ , as well as a decreased vascular formation in the adult retina in elmo1-/ , but an increased vascular formation in the adult elmo3-/ retinas. The phenotypical comparison provided few similarities, as increased Bowman space areas in adult elmo1-/ and elmo2 / kidneys, an increased hyaloid vessel diameter in elmo1-/ and elmo3 / and a transcriptional downregulation of the vascular development in elmo1-/ , elmo2 / , and elmo3 /- zebrafish larvae. Besides this, elmo1-/ , elmo2 / , and elmo3 /- zebrafish exhibited several distinct changes in the vascular and glomerular structure and in the metabolome and the transcriptome. Especially, elmo3 /- zebrafish showed extensive differences in the larval transcriptome and an impaired survivability. Together, the data demonstrated that the three zebrafish Elmo proteins regulate not only similar but also divergent biological processes and mechanisms and show a low functional redundancy.